Asupan zink dan magnesium makanan dengan disfungsi ereksi pada penderita sindrom metabolik - Saraheni Saraheni; I Dewa Putu Pramantara; Herni Astuti (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2014)
Background: Metabolic syndrome (MetS) is a disease of disorder of lipid and nonlipid metabolism. The West of Scotland Coronary Prevention Study found that men with MetS had probability 3.7 dysfunctions of erection (ED) by using International Index of Erectile Function (IIEF). Patient with heart disease had the risk 2 times to get ED, hypertension was 1.5-2 times, DM was 3-4 times, depression was 2-3.5 times, testosterone deficiency syndrome (TDS) was 1.5-2 times, and high cholesterol was 4 times. The nutrient deficiency of zinc (Zn) and magnesium (Mg) was suspected being the main component which had a role in resisting a sexuality growth and maturation process.Objective: Knowing the correlation of Zn and Mg feeding with erection dysfunction in MetS person.Method: This study was observational analytic study, with case-control design in the patient aged 30-60 years old. The respondent in this study was people with MetS according to WHO criterion. There was 82 patient divided into two groups, consist of 41 cases of MetS and ED, 41 cases with the normal patient. The data collected by interview, laboratory assessment and anthropometric measurement. The data analysis using univariate, bivariate and multivariate analysis using multiple logistic regression.Results: There was significant correlation between Zn feeding and ED (OR=7.15; 95% Cl=1.47-34.71; p=0.007) and there was significant correlation between Mg feeding with ED (OR=3.34; 95% Cl=1.07-10.4; p=0.033). The end result of the multivariate analysis showed the risk variable to the ED event, that was Zn feeding with OR=15.41. If the intake of Zn accompanied with risk factors associated as a cause of ED, multivariate analysis showed HbA1c’s degree with OR=12.57; triglyceride (OR=10.47); blood pressure (OR=5.82); and abdominal obesity (OR=6.94). The result shows that these risk factors can aggravate or anticipate the onset of dysfunction erection beside low Zn intake.Conclusion: There was statistically significant correlation between Zn and Mg feeding with erection dysfunction in MetS patient.